The Influence of Perceived Organizational Support, Work-Life Balance, Work Engagement, and Challenge Leadership on Turnover Intention Through Happiness at Work as an Intervening Variable Among Staff Employees at Pt. Cakrawala Putra Bersama, Tapin Regency, - Sutrisno; Pamungkas, Anton Respati; Sinaga, Henri; Kadir, Abdul (Archives of Business Research, 2024)
This study aims to analyze the influence of perceived organizational support, work life balance, work engagement, and challenge leadership on turnover intention through the variable happiness at work as an intervening variable in staff employees of PT Cakrawala Putra Bersama, Tapin Regency, South Kalimantan. The population in this study was all 70 staff at PT Cakrawala Putra Bersama. The sampling technique uses saturated sampling, where the entire population of 70 employees is used as the research sample. Data collection methods in this research are interviews, questionnaires, literature study, documentation and observation. This research uses the Smart PLS analysis tool. Hasil penelitian menjelaskan : 1) Perceived Organizational Support, Work-Life Balance, Work Engagement dan Challenge Leadership berpengaruh terhadap Happiness At Work pada PT. Cakrawala Putra Bersama. 2) Perceived Organizational Support, Work-Life Balance, Work Engagement dan Challenge Leadership berpengaruh terhadap Turnover Intention pada PT. Cakrawala Putra Bersama. 3) Happiness At Work berpengaruh terhadap Turnover Intention pada PT. Cakrawala Putra Bersama. 4) Happiness At Work memediasi pengaruh Perceived Organizational Support, Work-Life Balance, Work Engagement, Challenge Leadership terhadap Happiness At Work pada PT. Cakrawala Putra Bersama